Cognitive Trust di Dalam Bisnis Keluarga (Studi Kasus pada PT Dharma Samudera Fishing Industries tbk.) - Christina, Christina; Paulina, Paulina; Saputra, Teddy (UNUSA Press, 2016)
Family business experts suggested that family business is a cyclical cycle of trust that must be kept and maintained by all members of the family in order to maintain the harmonization of relations between the company and the family. The family business is certainly not immune from the variety of issues that are sometimes difficult to solve. One problem is the mistrust among the members of the family. As a result, it is often family business in decline, even forced to close as a result of the ongoing conflict. This study aims to explore the beliefs, especially cognitive trust of first and second generation at PT Dharma Samudera Fishing Industries Tbk. The method used in this research is qualitative descriptive. Results showed that inter-personal trust and confidence of competence has awakened among first and second generation, but the first generation not yet demonstrated their confidence in the system that strives to be built and run by the secondgeneration. They deepened the distrust their generation gap that occurred and led to the second generation chose to leave the company.